Perancangan Cerita Rakyat Sangkuriang Menggunakan Teknik Video Mapping - Andri Setiawan (PANTUN: Jurnal Ilmiah Seni Budaya, 2022)
The story of Sangkuriang or known as the legend of Mount Tangkuban Parahu, is a folklore living and developing in Indonesian society, especially in West Java. Sangkuriang is a local wisdom of the Sundanese which is full of messages, meanings and morals which can be learned and applied in everyday life by children. The development of technology and digital media allows everyone toaccess unlimited information. The easy access provides an opportunity to preserve cultural wealth with local wisdom values in digital packaging. Video mapping model is used to package the famous Sangkuriang legend in West Java. Video mapping is a technique of playing with projected light intoa certain area so that it is expected to atract children’s interest with more relevant media. This work uses design thinking theory and uses the 4p innovation approach from Chris Aton (2002). The creative work in producing the video mapping of Sangkuriang legend provides an alternative model for preserving the local wisdom values of Sangkuriang folklore which is more atractive and more accessible digitally.Keywords: Sangkuriang Folklore, Video Mapping, New Media  ABSTRAKPesatnya perkembangan teknologi membuat setiap individu dapat mengakses sebuah informasi dengan mudah dan berbanding lurus dengan perkembangan media dalam menyampaikan sebuah informasi. Munculnya media - media baru (new media) yang berbasis teknologi dapat dijadikan sarana inovasi dalam mengembangkan cerita rakyat Sangkuriang menjadi bentuk yang lebih baru dan dapat menjadi nilai lebih dalam membangun minat anak untuk mendalami cerita rakyat Sangkuriang yang merupakan kearifan lokal masyarakat Sunda. Salah satu media baru (new media) yang dapat kolaborasikan dengan cerita rakyat Sangkuriang adalah video mapping, Video mapping merupakan salah satu teknik memainkan cahaya yang diproyeksikan terhadap bidang tertentu, dibuat dengan teknik-teknik tertentu sehingga menimbulkan ilusi optik. Metodelogi dalam perancangan video mapping menggunakan metode “Design Thingking” atau cara berpikir desain dalam mencari  inovasi.